Mukhtar Yahya and the Method of Teaching Arabic: Analysis of Muhadasah Method in the Perspective of Behaviorism Theory - mujahid mujahid (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
This research aims to explore about Mukhtar Yahya and his thoughts on Muhadasah method in learning Arabic which was analyzed by learning theory of behaviorism. This is a qualitative research with historical and psychological approaches. The historical approach is used since Mukhtar Yahya as the figure had passed away. While the psychological approach is used to analyze Muktar Yahya's Muhadasah method. The results show first, Mukhtar Yahya was a figure who had a big role for the birth of PTAIN and IAIN Sunan Kalijaga. During his role in PTAIN and IAIN Sunan Kalijaga, Mukhtar Yahya held important positions, even Mukhtar Yahya often had double positions in IAIN. In his academic career, Mukhtar Yahya was a highly qualified intellectual in the fields of religion and Arabic language. His ability was influenced by his intellectual brilliance and accompanied by a high spirit in studying religion. Second, the psychological approach shows that the Muhadasah method of Mukhtar Yahya was strongly influenced by behaviorism learning theory. Although Mukhtar Yahya did not say that his methods were influenced by behaviorism learning theory, but the theory was highly visible in learning steps of Muhadasah. In Muhadasah method, learning process will occur due to the presence of stimulus which then produces learning responses from students.